Strategi Pemasaran Syariah Dalam Upaya Menarik Minat Nasabah Pada Bank Wakaf Mikro Pesantren Mawaridussalam - Pratama, Risky; Edi, Sarwo (Universitas Labuhanbatu, 2024)
This research was conducted to determine the sharia marketing strategy of the Mawaridussalam Islamic Boarding School Micro Waqf Bank in an effort to attract customers. Informants in the research are the Head of Management, Supervisor, and Operations Manager. Research methods used by collecting data, namely observation, interviews, and documentation. The discussion technique used in this research is qualitative descriptive. The results of this study show that in the implementation of sharia marketing strategies at the Mawaridussalam Islamic Boarding School Micro Waqf Bank by doing how to select prospective customer criteria, Muslim women who wear hijab and are married, behave well, have a business, and by approaching strategies with ustadzh, village heads, and study mothers in order to socialize to the community and business actors about what a Micro Waqf Bank is. As for the constraints and obstacles in the training process, prospective customers are still selfish, lack of care, especially when conducting socialization.